2021
DOI: 10.1136/thoraxjnl-2021-217782
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effects of combining azithromycin with inhaled tobramycin forP. aeruginosain cystic fibrosis: a randomised, controlled clinical trial

Abstract: RationaleInhaled tobramycin and oral azithromycin are common chronic therapies in people with cystic fibrosis and Pseudomonas aeruginosa airway infection. Some studies have shown that azithromycin can reduce the ability of tobramycin to kill P. aeruginosa. This trial was done to test the effects of combining azithromycin with inhaled tobramycin on clinical and microbiological outcomes in people already using inhaled tobramycin. We theorised that those randomised to placebo (no azithromycin) would have greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…45 In the United States, the PROMISE study (A Prospective Study to Evaluate Biological and Clinical Effects of Significantly Corrected CFTR Function) consisted of 480 PwCF followed both before and after starting ETI. 46 In the first 6 months, clinical outcomes improved (FEV1pp, BMI, CFQ-R respiratory domain) despite decreases in pulmonary maintenance medication usage (decreases in dornase alfa 6%, hypertonic saline 9.8%, azithromycin 9.1%, and inhaled antibiotics 34%). Despite these changes in baseline care, the effects seen in the real-world setting were similar to the clinical trial.…”
Section: Cf Modulatorsmentioning
confidence: 93%
See 2 more Smart Citations
“…45 In the United States, the PROMISE study (A Prospective Study to Evaluate Biological and Clinical Effects of Significantly Corrected CFTR Function) consisted of 480 PwCF followed both before and after starting ETI. 46 In the first 6 months, clinical outcomes improved (FEV1pp, BMI, CFQ-R respiratory domain) despite decreases in pulmonary maintenance medication usage (decreases in dornase alfa 6%, hypertonic saline 9.8%, azithromycin 9.1%, and inhaled antibiotics 34%). Despite these changes in baseline care, the effects seen in the real-world setting were similar to the clinical trial.…”
Section: Cf Modulatorsmentioning
confidence: 93%
“…Of interest, in the first 6 months of ETI, a correlation found that for each additional 10-point decrease in SC, an additional 0.89% increase in FEV1pp was seen, with a larger improvement seen in females. 46 ETI has also changed lung transplantation. The French CF centers reported on the 65 PwCF who were lung transplant candidates (listed or under evaluation) who started on ETI, two received transplants within days of starting ETI, while the rest showed improvements in FEV1pp, weight, BMI, decreases in intravenous (IV) antibiotic use, hospitalizations, oxygen use, noninvasive ventilation, and gastrostomy T A B L E 1 Case reports of interest related to ETI use in people with cystic fibrosis.…”
Section: Cf Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial protocol specified ANOVA at the interim analysis and ANCOVA at the final analysis, using the weight-for-age z-score at visit 3 as a covariate. The TEACH trial was an RCT of 108 people over 12 years old to evaluate the effect of adding oral azithromycin to inhaled tobramycin on lung function in people with CF who are also chronically infected with Pseudomonas aeruginosa (Nichols et al, 2021). The trial protocol specified ANOVA at two interim analyses (after 50% and 75% accrual) and a final analysis with ANCOVA using the randomization strata as a covariate.…”
Section: Simulation Parametersmentioning
confidence: 99%
“…The Testing the Effect of Adding Chronic Oral Azithromycin to Inhaled Tobramycin in People with Cystic Fibrosis (TEACH) trial (NCT02677701) illustrates these points 2. TEACH was a randomised, placebo-controlled, double-blinded study examining the effect of azithromycin therapy on the short-term efficacy of inhaled tobramycin in people with CF and Pseudomonas aeruginosa infection.…”
mentioning
confidence: 99%